(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This chapter comprehensively analyzes the pedagogical and psychological significance of studying birds in biology education. The research explores the role of birds in developing cognitive skills, enhancing scientific literacy, improving students’ mental well-being, and fostering responsible environmental attitudes. Based on biophilia theory and nature-based learning approaches, the integration of bird observation into the educational process is shown to increase student motivation, reduce stress levels, and strengthen ecological ethics. The chapter synthesizes existing scientific literature and provides practical recommendations.